Penyelenggaraan Administrasi Di Bagian Umum Pemerintahan Sekretariat DPRD Provinsi Sumatera Utara - Sumiati, Sumiati; Harahap, R. Hamdani; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The research objective was to analyze Administration in the general government section of the DPRD Secretariat in North Sumatra Province. Obstacles in administering administration in the general section of the DPRD Provincial Secretariat of North Sumatra. The research method used was descriptive with qualitative analysis. Data collection was obtained from interviews, documentation, and observations. The results of the study are the Secretariat of the Provsu DPRD prepares the target of activities by calculating each type of activity carried out by the Regional Representative Council of North Sumatra Province. Synchronization of these three things greatly determines the success of the Provsu DPRD Secretariat in carrying out the tasks of secretarial administration and financial administration. Provsu DPRD has carried out the general principles of good governance including transparency and participation. In order to improve performance, the DPRD of North Sumatra Province has carried out its duties, functions and authorities to be more efficient and effective. That the role of the Expert Staff and Expert Team / Expert Group in supporting the smooth implementation of the tasks and functions of the Provsu DPRD is very strategic. While the suggestions from this study are Â Improving employee work competencies through training. Improving more effective coordination between the Council Secretariat and the DPRD. Secretariat employees are more responsible. The Chairperson of the DPRD Secretariat must be firm and be dealt with if there are those who are lazy to go to work or violate, so that staff or all those who work in the Secretrariat really change their attitude that is not disciplined.